SpeakApp-Kids! Virtual reality training to reduce fear of public speaking in children – A proof of concept. (March 2022) - Sülter, Robin E.; Ketelaar, Paul E.; Lange, Wolf-Gero
Abstract: Virtual reality exposure therapy (VRET) is a promising tool to reduce public speaking anxiety in adults, while treatment and prevention of public speaking anxiety in children has been largely neglected. We examined whether repeated brief exposures to a virtual audience embedded in a prototype of the Virtual Reality (VR) SpeakApp-Kids! helped to reduce (1) self-reported state anxiety during three public speaking practice sessions, (2) state anxiety during the actual presentation that followed, and (3) general public speaking anxiety from the first practice session until after the actual presentation in children aged 9–12 years ( n  = 40). First, we found a decrease in state anxiety during the first two practice sessions. Also in line with our expectations, pupils in the SpeakApp-Kids! condition reported lower state anxiety during the actual presentation than the control (at home) condition ( n  = 49). Finally, we found a larger decrease in general public speaking anxiety from the first practice session until one week after the actual presentation for the SpeakApp-Kids! condition, as compared to the control children preparing their presentations as usual. Taking limitations into account, this VR SpeakApp-Kids! is a promising tool to be developed further as it has potential to serve as an educational tool for speech practice and thereby reducing public speaking anxiety. More importantly, it has potential to prevent public speaking anxiety from developing in the first place. Highlights: Children experienced less state anxiety across practice with the SpeakApp-Kids!. SpeakApp-Kids! practice reduced state anxiety during the actual talk. SpeakApp-Kids! practice reduced fear of public speaking in general. The SpeakApp-Kids! is important as an educational tool to practice. The SpeakApp-Kids! potentially prevents public speaking anxiety from developing.